Inverse form finding with H-adaptivity and an application to a notch stamping process - Caspari, Michael; Landkammer, Philipp; Steinmann, Paul (Proceedings of the 14th International Conference on Computational Plasticity - Fundamentals and Applications, 2017)
The aim is to determine the optimized semi-finished workpiece geometry to its given target geometry after a forming process. Hereby, a novel approach for inverse form finding, a type of a shape optimization, is applied to a notch stamping process. As a special feature, h-adaptive mesh refinement is considered within the iteratively performed forming simulatio
Keywords: H-adaptivity; Inverse form finding; Metal forming; Shape optimization